State of the Art – How I manage coagulopathy in cardiac surgery patients. (23rd January 2014) - Davidson, Simon
Summary Over 35 000 cardiac operations using cardiopulmonary bypass are performed annually in the UK. Post‐operative bleeding is a common cause of morbidity. Although there have been improvements in surgical techniques, recent publications still show post‐operative blood loss to be significant, with allogeneic blood product usage as high as 50%. Despite greater understanding of the mechanisms of the coagulopathy encountered during cardiac surgery the development of treatment options has been slow. There has been a realization of the inadequacy of fresh frozen plasma to correct the coagulopathy in this setting, leading to greater off‐label use of specific factor concentrates to stop bleeding, e.g., prothrombin complex concentrates and fibrinogen concentrates. Recent trials using factor XIII and IX concentrates have not been successful. This article will review preventative measures to reduce post‐operative bleeding and the current management of bleeding with such factor concentrates and, in most cases, the limited evidence supporting their widespread use.